Penerapan Kurikulum Madrasah Berbasis Keagamaan dengan Pendekatan Bilingual di MAK Al Hikmah 02 Benda, Sirampog, Brebes - Hanifah, Nur; Mondari, Mondari; Solihatudiniyah, Lela Salamah; Erihadiana, Mohamad (CV. Rayyan Dwi Bharata, 2025)
This study aims to analyze the implementation of a religious-based curriculum with a bilingual approach in madrasas as an effort to produce a generation with noble character and global competitiveness. This curriculum is designed to combine learning based on Islamic values with mastery of international languages, such as Arabic and English, in order to equip students with scientific competence and cross-cultural communication skills. The research method used involves a qualitative approach through observation, interviews, and analysis of curriculum documents. The results of the study indicate that the bilingual approach in learning in madrasas has a positive impact on students' understanding of religious teachings while improving their international language skills. In addition, the integration of religious education and global competence allows students to be better prepared to face the challenges of the modern world without leaving the roots of Islamic values